Variety of genotypes of a HCV virus and outcomes of chronic hepatitis C: results 5 summer supervision in the territory of the Kirov region - S. V. Baramzina; A. L. Bondarenko; O. N. Liubeznova; G. M. Zianchurina (Журнал инфектологии)
The analysis of the epidemiological situation in respect of chronic hepatitis C in the Russian Federation and the Kirov region for the period 1998–2012 yy. The data on the characteristics and frequency of outcomes of chronic hepatitis C, according to the 5-year observation of patients Kirov branch of viral hepatitis infectious diseases hospital. The results of genotyping HCV-virus in 730 patients with chronic hepatitis C in the dynamics from 2006–2010, and in comparison with other regions of Russia. Dominant in the region are the genotypes 1b and 3a, minor – 2 and 1a. During the analyzed period, there was a trend to a decrease in the proportion of genotypes 1b and 1a, and increase the proportion of subtype 3a and 2.